2009
DOI: 10.1002/hbm.20718
|View full text |Cite
|
Sign up to set email alerts
|

Coordinate‐based activation likelihood estimation meta‐analysis of neuroimaging data: A random‐effects approach based on empirical estimates of spatial uncertainty

Abstract: A widely used technique for coordinate-based meta-analyses of neuroimaging data is activation likelihood estimation (ALE). ALE assesses the overlap between foci based on modelling them as probability distributions centred at the respective coordinates. Here we present a revised ALE algorithm addressing drawbacks associated with former implementations:The first change pertains to the size of the probability distributions, which had to be specified by the used. To provide a more principled solution, we analysed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
2,003
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 1,725 publications
(2,011 citation statements)
references
References 88 publications
5
2,003
0
3
Order By: Relevance
“…One possibility is that, during recognition memory decisions, lateral IPS serves as a "mnemonic accumulator" of signals (Eickhoff et al 2009) of relevant studies in the memory and attention literatures (thresholded with a FDR of all P < 0.05, orange; overlap rendered in yellow). Comparison of the findings in the current study to those reported in the literature reveals overlap between (b) the IPS region displaying memory strength effects here and the IPS region consistently associated with familiarity across studies of episodic retrieval (as compiled in Vilberg and Rugg 2008b), (c) the SPL region positively tracking retrieval reaction time here and the SPL region that is consistently associated with top-down attention across studies of attention (as compiled in Hutchinson et al 2009), (d) the AnG region displaying successful recollection effects here and the AnG region consistently associated with recollection across studies of episodic retrieval (as compiled in Vilberg and Rugg 2008b), and (e) the left TPJ region displaying greater activity for Item Only than for Task and Specific Source trials here and the TPJ region consistently associated with the stimulus-driven reflexive orienting of attention across studies of attention (as compiled in Hutchinson et al 2009).…”
Section: Dorsal Ppc: Lateral Ips Versus Splmentioning
confidence: 99%
See 1 more Smart Citation
“…One possibility is that, during recognition memory decisions, lateral IPS serves as a "mnemonic accumulator" of signals (Eickhoff et al 2009) of relevant studies in the memory and attention literatures (thresholded with a FDR of all P < 0.05, orange; overlap rendered in yellow). Comparison of the findings in the current study to those reported in the literature reveals overlap between (b) the IPS region displaying memory strength effects here and the IPS region consistently associated with familiarity across studies of episodic retrieval (as compiled in Vilberg and Rugg 2008b), (c) the SPL region positively tracking retrieval reaction time here and the SPL region that is consistently associated with top-down attention across studies of attention (as compiled in Hutchinson et al 2009), (d) the AnG region displaying successful recollection effects here and the AnG region consistently associated with recollection across studies of episodic retrieval (as compiled in Vilberg and Rugg 2008b), and (e) the left TPJ region displaying greater activity for Item Only than for Task and Specific Source trials here and the TPJ region consistently associated with the stimulus-driven reflexive orienting of attention across studies of attention (as compiled in Hutchinson et al 2009).…”
Section: Dorsal Ppc: Lateral Ips Versus Splmentioning
confidence: 99%
“…Comparison of the findings in the current study to those reported in the literature reveals overlap between (b) the IPS region displaying memory strength effects here and the IPS region consistently associated with familiarity across studies of episodic retrieval (as compiled in Vilberg and Rugg 2008b), (c) the SPL region positively tracking retrieval reaction time here and the SPL region that is consistently associated with top-down attention across studies of attention (as compiled in Hutchinson et al 2009), (d) the AnG region displaying successful recollection effects here and the AnG region consistently associated with recollection across studies of episodic retrieval (as compiled in Vilberg and Rugg 2008b), and (e) the left TPJ region displaying greater activity for Item Only than for Task and Specific Source trials here and the TPJ region consistently associated with the stimulus-driven reflexive orienting of attention across studies of attention (as compiled in Hutchinson et al 2009). Note that only left parietal peak-voxel coordinates were used in the generation of the ALE maps, whereas the bootstrapped null distribution to which they were compared necessarily included voxels throughout the brain (Eickhoff et al 2009). This slightly lowered the resulting P values (and consequently produced more liberal estimates of activation in the ALE maps).…”
Section: Dorsal Ppc: Lateral Ips Versus Splmentioning
confidence: 99%
“…The meta‐analysis was performed using the ALE algorithm (Eickhoff et al., 2009, 2012; Turkeltaub et al., 2012) found in the GingerALE2.3 software (http://brainmap.org/ale/; RRID:SCR_014921). In the ALE approach, spatial probability distributions for the foci were modeled at the center of three‐dimensional Gaussian functions and the Gaussian distributions were aggregated across the entire set of experiments to generate a map of consistencies among studies that estimated the likelihood of activation for each voxel—the ALE statistic (Eickhoff et al., 2009).…”
Section: Methodsmentioning
confidence: 99%
“…In the ALE approach, spatial probability distributions for the foci were modeled at the center of three‐dimensional Gaussian functions and the Gaussian distributions were aggregated across the entire set of experiments to generate a map of consistencies among studies that estimated the likelihood of activation for each voxel—the ALE statistic (Eickhoff et al., 2009). Coordinates reported in the Talairach space were first transformed into the Montreal Neurological Institute brain template using the appropriate transformation algorithms implemented in GingerALE.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation